The Dynamics of Community Social Construction in the Implementation of Public Policy for Child Protection - Idyaningsih, Nining; Rossydi, Ahmad; Fachrurrazy, Fachrurrazy (IJORER : International Journal of Recent Educational Research, 2026)
This study examines the dynamics of community social construction in the implementation of child protection policies in Indonesia, focusing on public perceptions, participation, and social practices at the local level. Despite the existence of comprehensive child protection regulations, cases of violence against children remain high, indicating a persistent gap between normative policies and their practical implementation. This research employed a qualitative case study approach conducted in three major Indonesian cities: Surabaya, Yogyakarta, and Makassar. Data were collected through in-depth interviews, participatory observation, and document analysis involving community members, educators, government officials, and child protection stakeholders. The findings reveal that cultural norms, educational background, and access to information significantly influence community understanding of child protection policies. Although most participants were aware of child protection regulations, active involvement in violence prevention and reporting mechanisms remained limited. The study also found that violence-based parenting practices are still socially normalized in some communities, hindering effective policy implementation. The study concludes that strengthening community engagement, cross-sector collaboration, and public education is essential to improving the effectiveness of child protection policies and fostering a child-friendly social environment in Indonesia.